3D printing nanocomposites with controllable "strength-toughness" transition: Modification of SiO2 and construction of Stereocomplex Crystallites. (8th February 2022) - Lyu, Yang; Wen, Xinlong; Wang, Gongliang; Zhang, Qinghong; Lin, Leyu; Schlarb, Alois K.; Shi, Xinyan
Abstract: Modified nanoparticles are increasingly being used in the manufacture of multi-purpose polymers of high-performance. Most modifications only focus on the improvement of strength or toughness of the composite materials. These adjustments are however limited by the traditional molding method. In this paper, low molecular weight poly (d -lactic acid) (PDLA) was coated on the surface of silica dioxide (SiO2) using the green chemical method. This realized nano dispersion of SiO2 in the poly (L-lactic acid)/poly (butylene adipate terephthalate) biodegradable blend (PLLA/PBAT) and uniform distribution of Stereocomplex Crystallites (SC) in the matrix. The mechanical properties of composites were dependent on their crystallization behavior, which was influenced by the temperature of 3D printing nozzle to achieve the "strength-toughness" transition. The PDLA modified SiO2 (SiO2-PDLA) evenly nano dispersed in the composite, and it did not agglomerate even at 5 wt %. The heat resistance of the composites improved with an increase in SiO2-PDLA, attributed to the SC. At a temperature of the 3D printing nozzle of 180 °C, the tensile strength of composites was greatly enhanced by the distribution of SC and SiO2-PDLA in the composite material. At a nozzle temperature of 210 °C, the SC melted. The PDLA grafted on SiO2 can act as a low molecular weight plasticizer to improve the toughness of composites. Graphical abstract: Image 1